2021
DOI: 10.24252/mapan.2021v9n2a5
|View full text |Cite
|
Sign up to set email alerts
|

Calculus Learning via Screencast-O-Matic During the Pandemic: An Exploration Towards Students’ Perception of Math Anxiety

Abstract: The emergence of the Covid-19 pandemic has transformed the learning system into an online mode, where students' anxiety became the spotlight for educators to create a learning environment that actively engages them. Many educators are competing in maximizing the use of technology to ensure students are engaged in the learning process. The study aims to explore students’ perception of math anxiety through the implementation of Screencast-O-Matic in calculus learning. This study involves 41 students at the unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The demonstration in the video is not only easily replicable by viewers, but the commentary also provides a greater comprehension of each of the steps shown. According to a study on learning calculus via ScreenPal (formerly known as Screencast-O-Matic) conducted in Indonesia, while developing educational videos, the message to be transmitted must be clear and precise, user-friendly, have good visualisation, and be accessible at any time and from any location [22]. Previous studies have shown that videos are more of a supplement tool to support the learning of specific topics exclusively [23].…”
Section: B Screencast Video Usage In Online Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The demonstration in the video is not only easily replicable by viewers, but the commentary also provides a greater comprehension of each of the steps shown. According to a study on learning calculus via ScreenPal (formerly known as Screencast-O-Matic) conducted in Indonesia, while developing educational videos, the message to be transmitted must be clear and precise, user-friendly, have good visualisation, and be accessible at any time and from any location [22]. Previous studies have shown that videos are more of a supplement tool to support the learning of specific topics exclusively [23].…”
Section: B Screencast Video Usage In Online Learningmentioning
confidence: 99%
“…YouTube is one of the most popular platforms for finding a variety of screencast tutorials. Screencasts are a go-to option because of the visual guidance and ease of learning, and have been implemented in a variety of educational settings, including mathematics [17,22], computer science [18,26], and statistics [23,28], to name a few.…”
Section: B Screencast Video Usage In Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Media merupakan suatu alat yang dapat digunakan guru untuk menyampaikan materi pembelajaran kepada siswa agar mudah diterima dan mudah dipahami oleh siswa (Sudarsono, 2021). Media yang dipilih guru untuk digunakan dalam pemeblajaran harus mudah dimengerti siswa dan mudah digunakan (Soesanto and Dirgantoro, 2021). Selain itu media yang digunakan harus mudah diperoleh sehingga tidak menyulitkan guru maupun siswa dalam mencari media tersebut.…”
Section: Pendahuluanunclassified
“…In context of learning in remote areas and among students with lowsocio-economic status, the simple application called WhatsApp has been adopted as learning media which further assisted the process of mathematics learning (Raynal & Light, 2021;Wong, 2020;Wulandari & Mandasari, 2021). Moreover, the presence of technology platforms in supporting mathematics education has shown positive impacts as reducing anxiety (Delima & Cahyawati, 2021;Soesanto & Dirgantoro, 2021a;Varghese, 2020), improving students' learning (Kalogeropoulos et al, 2021), and improving students' motivation for learning (Randall, 2022;Seidu & Owusu-boateng, 2022). Besides, Information and Communications Technology (ICT) innovation used in mathematics education has grown rapidly, and thus affected the percentage of mobile devices usage among teachers and students (Alabdulaziz, 2021;Gaol & Hutagalung, 2020;Rachmavita, 2020).…”
mentioning
confidence: 99%